Vulnerability and Blood Donation: Enhancing Safety While Combating Stigma in Colombia - García-Otálora, Michel; Pinto Bustamante, Boris; Ochoa-Cómbita, María; Pardo-Cubillos, María; Quintero-Consuegra, Miguel (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
In 2022, the Colombian Constitutional Court mandated the removal of the 12-month deferral for blood donation for potential male donors who reported having had sexual relations with other men in the past year in the national guidelines for blood donor selection, aiming to combat stigma and discrimination against diverse sex-gender identities. This article explores the complex dynamics of this mandate, and examines the tension between private moral values, like self-determination and freedom of expression, with public values, such as non-maleficence, equality and vulnerability approach. The analysis delves into the challenges of Colombia’s hemovigilance system, the epidemiological patterns of HIV, and the lack of supporting studies for these guideline changes. Structural and logistical constraints in minimizing transfusion risks are highlighted, emphasizing the need for improved safety measures. The implications of reduced deferral times for high-risk groups without adequate testing protocols are also addressed. The necessity for national studies to determine the actual risk posed by different populations is underscored, advocating for robust safety measures, including universal nucleic acid testing (NAT), to protect both donors and recipients. Balancing the elimination of discrimination with enhanced blood safety practices is crucial to ensure non-maleficence and equity for all stakeholders involved in the blood donation process in Colombia. The article emphasizes the importance of protecting individuals and communities at greater risk of defenselessness and insecurity within the evolving landscape of blood donation protocols.